UMA ABELHA NA CHUVA E A CONCIÊNCIA DAS CONSTANTES TRANSFORMAÇÕES DO MUNDO PORTUGUÊS - Remédios, Maria Luíza Ritzel (Letras, 2000)
UMA ABELHA NA CHUVA E A CONCIÊNCIA DAS CONSTANTES TRANSFORMAÇÕES DO MUNDO PORTUGUÊS